Answer: -3x+13
Step-by-step explanation: Combine like terms (-4x + x) and (5 + 8)
-4x + x = -3x
5 + 8 = 13
Hope this helps! If it doesn't, I'm sorry!
B) 0
C) 4
D) 8
Answer:y = 0.8x and y = -0.12x2 + 20
Step-by-step explanation:
Triangle is both acute and scalene.
A polygon with three edges and three vertices is called a triangle. It is one of the fundamental geometric shapes. Triangle ABC is the designation for a triangle with vertices A, B, and C. In Euclidean geometry, any three points that are not collinear produce a distinct triangle and a distinct plane.
here, we have,
we know that,
A scalene triangle has three unequal sides and angles, whereas an acute triangle has three acute angles (measured fewer than 90 degrees). Consequently, the characteristics of an acute scalene triangle are as follows: three lines that cross each other. a trio of sharp angles All sides are not equal.
Given
All angles are less than 90 degrees so it is acute. The sides are of difference lengths so it is scalene.
To know more about acute triangles refer to :
#SPJ7
x = –1
No Real Solutions
x = 11 and x = 1
x = 11
The solution to the quadratic equation x² - 12x + 11 = 0 is x = 11 and x = 1.
Given the quadratic equation in the question:
x² - 12x + 11 = 0
To solve the quadratic equation x² - 12x + 11 = 0 by completing the square, first the constant term to the other side of the equation:
x² - 12x + 11 = 0
x² - 12x + 11 - 11 = 0 - 11
x² - 12x = -11
Next, find the value that is equal to the square of half of b:
( b/2 )² = ( -12/2 )² = (-6)²
Add (-6)² to each side of the equation:
x² - 12x + (-6)² = -11 + (-6)²
x² - 12x + 36 = -11 + 36
x² - 12x + 36 = 25
Factor the perfect trinomial sqaure:
( x - 6 )² = 25
Solve for x:
x - 6 = ±√25
x - 6 = ±5
x = 6 ± 5
Hence, x = 6 - 5 = 1
And x = 6 + 5 = 11.
Therefore, the values of x are 1 and 11.
Learn more about quadratic equations here: brainly.com/question/1863222
#SPJ3
Answer:
Step-by-step explanation:
x^2 – 12x + 11 = 0
(x-11)(x-1)
x= 11, 1 completing the square